Land Use and Land Cover in Akure City, Ondo State, Nigeria, Using GIS and Remote Sensing - Olabode, Abiodun Daniel (Asian Journal of Science, Technology, Engineering, and Art, 2026)
Urbanization and industrial development have intensified pressure on forest reserves in cities and settlement areas, increasing the vulnerability of urban forests to land-use change. This study examines the effects of land-use changes on forest encroachment in Akure City, Ondo State, Nigeria. A remote sensing and GIS-based approach was employed using satellite imagery obtained from the United States Geological Survey (USGS) for 2000, 2010, and 2020. The images were processed and analyzed using ArcMap 10.5 and Environment for Visualizing Images (ENVI) software to assess changes in land-use and land-cover patterns over the study period. The findings reveal notable changes in Akure City’s land-use structure, with less dense forest accounting for 41%, 66%, and 58% in 2000, 2010, and 2020, respectively, while built-up areas increased from 1.53% in 2000 to 3.28% in 2010 and 5.28% in 2020. The loss of natural vegetation also increased substantially from 4.4 km² in 2000 to 9.34 km² in 2010 and 12.01 km² in 2020. Surface water bodies were nearly absent in 2000 but accounted for 0.93 km² in 2010 and 0.66 km² in 2020. These findings indicate that continued urban expansion and associated land-use changes are likely to accelerate forest encroachment in Akure City. The study contributes to urban environmental management by highlighting the need for government authorities at all levels to implement sustainable forest conservation strategies and integrated city management policies.